How Does Immunomodulatory Nanoceria Work? ROS and Immunometabolism - Ernst, Lena M.; Puntes, Victor (Frontiers in Immunology, 2022)
Dysregulation of the immune system is associated with an overproduction of metabolic reactive oxygen species (ROS) and consequent oxidative stress. By buffering excess ROS, cerium oxide (CeO2) nanoparticles (NPs) (nanoceria) not only protect from oxidative stress consequence of inflammation but also modulate the immune response towards inflammation resolution. Immunomodulation is the modulation (regulatory adjustment) of the immune system. It has natural and human-induced forms, and it is part of immunotherapy, in which immune responses are induced, amplified, attenuated, or prevented according to therapeutic goals. For decades, it has been observed that immune cells transform from relative metabolic quiescence to a highly active metabolic state during activation. These changes in metabolism affect fate and function over a broad range of timescales and cell types, always correlated to metabolic changes closely associated with mitochondria number and morphology. The question is how to control the immunochemical potential, thereby regulating the immune response, by administering cellular power supply. In this regard, immune cells show different general catabolic modes relative to their activation status, linked to their specific functions (maintenance, scavenging, defense, resolution, and repair) that can be correlated to different ROS requirements and production. Properly formulated, nanoceria is highly soluble, safe, and potentially biodegradable, and it may overcome current antioxidant substances limitations and thus open a new era for human health management.